Pengaruh Kreativitas Dan Dukungan Keluarga Terhadap Motivasi Berwirausaha Siswa Program Keahlian Kuliner Fase F Di SMK Negeri 6 Padang - Ufoi Naso Gowasa; Reni Respita; Serli Diovani Teza (Kilau Publishing, 2025)
This study aims to determine the extent to which:1) creativity influences the entrepreneurial motivation of students in the Culinary Expertise Program Phase F at SMK Negeri 6 Padang, 2) family support influences the entrepreneurial motivation of students in the same program, and 3) creativity and family support jointly influence the entrepreneurial motivation of students in the Culinary Expertise Program Phase F at SMK Negeri 6 Padang.This research employed a quantitative approach. The population consisted of 101 students from the Culinary Expertise Program Phase F at SMK Negeri 6 Padang. The sampling technique used was total sampling, in which the number of samples is equal to the total population.The results of this study indicate that: 1) Creativity has a positive and significant effect on the entrepreneurial motivation of students in the Culinary Expertise Program Phase F at SMK Negeri 6 Padang. This is evidenced by a t-value of 5.408, which is greater than the t-table value of 1.661, and a significance value of 0.000, which is less than 0.05. 2) Family support has a positive and significant effect on the entrepreneurial motivation of students in the Culinary Expertise Program Phase F at SMK Negeri 6 Padang. This is shown by a t-value of 2.000 > t-table 1.661 and a significance value of 0.048 < 0.05. 3) Creativity and family support together have a positive and significant effect on the entrepreneurial motivation of students in the Culinary Expertise Program Phase F at SMK Negeri 6 Padang. This is indicated by an F-value of 18.241 > F-table 3.09 and a significance value of 0.000, which is less than the 5% significance level (α = 0.05).